Spud learning to fly - Van de Ruit, John. (London : Penguin Books, 2011)
Warning: This book may cause frequent bouts of uncontrollable, hysterical laughter...Spud Milton (practically a man in most areas) is hoping for a smooth ride as he returns to boarding school as a senior. But instead he finds his vindictive arch-enemy is back to taunt him and a garrulous new boy has taken residence in his dorm, along with the regular inmates and misfits he calls friends. Spud's world has never felt more uncertain as he attempts to master Shakespeare, girls, religion and the meaning of life.Once again, armed only with his wits and his diary, Spud invites us on a hilarious journey deep into the sublime and ridiculous world of being a teenager.
Keywords: Milton, Spud (Fictitious character -- Fiction; Boarding schools -- South Africa -- Fiction; Private schools -- South Africa -- Fiction; Teenage boys -- South Africa -- Fiction; Teenage boys -- South Africa -- Fiction; Single-sex schools -- Fiction; Diary fiction